On Average Hub Number of a Graph - Mathad, Veena; Puneeth, S. (Communications in Mathematics and Applications, 2024)
The idea of local and average hub numbers is explored as an expansion of the hub number in graphs, a connectivity measure that holds significance in transportation networks. In this analysis, we investigate the characterization of graphs by examining the local and average hub numbers and study them for graph classes namely trees and thorn graphs. Additionally, we determine the precise values of the average hub number for certain graph operations and discuss the bounds of Nordhaus-Gaddum type inequalities.
Keywords: Hub set; Average hub number